Financial backing as an element of infrastructural support for agricultural development: Ukrainian realities - Krupin, Vitaliy; Chemerys, Vasyl (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
Abstract: This article sets out to investigate the current situation for financial backing of agricultural development in the Ukraine as an element of the complex infrastructural support for this type of economic activity. The research is based both on statistical data and its analysis, as well as on expert opinions of Ukrainian scientists, dealing with these particular issues.A number of components of the financial system were reviewed, including the activities of banks in financing of agricultural production, Ukrainian peculiarities and activities of credit unions, leasing and insurance companies, stock exchange markets, foreign and domestic investors, as well as the financial specificities in operation of local rural self-governance authorities and various inter-budgetary relations.The main conclusion is that Ukrainian financial backing of agricultural production remains inefficient, yet with proper measures, introduced in the future, it could become a proper tool for infrastructural support of producers and processors in agricultural sector of Ukrainian economy. It is a key requirement for being able to participate and be internationally competitive on agricultural and food markets.
Keywords: financial backing; infrastructure; agriculture; development; the Ukraine